High Growth and Low Consumption in East Asia : How to Improve Welfare While Avoiding Financial Failures - Rochon, Celine (IMF Working Papers; Working Paper, 2007)
This paper analyzes certain policies that are typical of a number of rapidly growing East Asian countries in which a fixed exchange rate, combined with a surplus labor market, has made domestic assets relatively inexpensive, generating high rates of FDI as well as domestic capital formation. This "investment hunger" can lead to unanticipated declines in the returns to investment, and resulting financial insolvencies. Private consumption remains low and there are concerns that high savings rates cannot be sustained. We construct a dynamic general equilibrium model and apply it to a stylized Asian economy, loosely based upon China. We calibrate a benchmark equilibrium, and carry out various counterfactual simulations to analyze alternative policies, in particular tax cuts and exchange rate revaluations, as instruments in increasing private consumption while avoiding bank failures.